Remarques sur la transformation des épithètes nfr ḫpr(.w) dans les cartouches du nom de naissance de Thoutmosis III - Biston-Moulin, Sebastien (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
Reconsideration of the question of recarving (or erasing) the epithet nfr ḫpr in the name of son of Re of Tuthmosis III. It was suggested that these alterations could be the work of Thutmose III himself. Several evidences from the temple of Amun-Ra at Karnak shows however that this hypothesis must be rejected. The changes have occurred after the Amarna period. Based on these observations a new hypothesis related to the close resemblance of the epithet with the praenomen of Amenhotep IV – Akhenaten is raised regarding the nature and distri-bution of these changes rather erratic in a temple or even on a single wall.